2010
DOI: 10.1007/s10561-009-9149-9
|View full text |Cite
|
Sign up to set email alerts
|

What tissue bankers should know about the use of allograft blood vessels

Abstract: Vascular allografts have been used by surgeons with varying levels of enthusiasm over the last 100 years, to treat a wide variety of vascular conditions. This article reviews the history of vascular allografts, the current indications for use, and the background to current retrieval, processing and cryopreservation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Allogeneic blood vessels play an important role in infected cardiac and vascular surgery [Nevelsteen et al, 1998;Leseche et al, 2001;Gabriel et al, 2004;Vardanian et al, 2009;Bisdas et al, 2010;Dodd, 2010]. The current state of the art for preserving human cardiovascular tissues, including arteries, is the conventional freezing cryopreservation (CFC) method, employing controlled-rate freezing with 10-20% dimethylsulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic blood vessels play an important role in infected cardiac and vascular surgery [Nevelsteen et al, 1998;Leseche et al, 2001;Gabriel et al, 2004;Vardanian et al, 2009;Bisdas et al, 2010;Dodd, 2010]. The current state of the art for preserving human cardiovascular tissues, including arteries, is the conventional freezing cryopreservation (CFC) method, employing controlled-rate freezing with 10-20% dimethylsulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…2 Other surgical approaches reported in the literature to restore arterial flow include the use of antibiotic impregnated surgical conduit grafts, the use of autologous superficial femoral vein grafts, endovascular stent grafting and the use of cadaveric arterial aortic allografts. 3 In this case, we felt the large intraabdominal septic burden and the patient's relatively young age (42 years) were reasons to try and avoid extra-anatomic bypass grafting if at all possible. Furthermore, the presence of bilateral DVTs precluded an attempt at using superficial veins for aortic reconstruction.…”
Section: Discussionmentioning
confidence: 88%
“…Although we undertake routine endovascular stent grafting for atherosclerotic aortic aneurysms in our unit, we were reluctant to consider this approach for fear of introducing foreign material into the aneurysm, particularly as endovascular stent grafting for MAAAs has been reported as only to be a potential bridge to open surgery. 3 Cryopreserved arterial allografts have been adopted successfully as a treatment for MAAAs in mainland Europe and the US. Allografts are retrieved from deceased donors and assessed against rejection criteria before being stored frozen indefinitely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile the authors reported the superiority of the method when compared to venous graft reconstruction due to the fact that arterial grafts have a lower risk of developing postoperative complications such as thrombosis, stenosis or infection (22). Therefore, it seems that arterial grafts are more resistant to surgical manipulation, do not have valves, are more effective in reducing the occlusion risk due to external visceral compression and are associated with a lower risk of graft infection (23,24).…”
Section: Discussionmentioning
confidence: 99%